Associations between surface markers on blood monocytes and carotid atherosclerosis in HIV‐positive individuals. Issue 2 (3rd December 2013) - Westhorpe, Clare L V; Maisa, Anna; Spelman, Tim; Hoy, Jennifer F; Dewar, Elizabeth M; Karapanagiotidis, Sofie; Hearps, Anna C; Cheng, Wan‐Jung; Trevillyan, Janine; Lewin, Sharon R; Sviridov, Dmitri; Elliott, Julian H; et al.
Abstract : Chronic HIV infection is associated with increased risk of cardiovascular disease (CVD), including in patients with virological suppression. Persistent innate immune activation may contribute to the development of CVD via activation of monocytes in these patients. We investigated whether changes in monocyte phenotype predict subclinical atherosclerosis in virologically suppressed HIV‐positive individuals with low cardiovascular risk. We enroled 51 virologically suppressed HIV‐positive individuals not receiving protease inhibitors or statins and 49 age‐matched uninfected controls in this study. Carotid artery intima‐media thickness (cIMT) was used as a surrogate marker for CVD, and traditional risk factors, including Framingham risk scores, were recorded. Markers of monocyte activation (CD14, CD16, CCR2, CX3CR1, CD38, HLA‐DR and CD11b) were measured in whole‐blood samples by flow cytometry. Associations were assessed using univariate and multivariate median regressions. Median cIMT was similar between HIV‐positive and HIV‐negative participants ( P =0.3), although HIV‐positive patients had significantly higher Framingham risk score ( P =0.009) and systemic inflammation. Expression of two monocyte markers, CD11b and CX3CR1, independently predicted carotid artery thickness in HIV‐positive individuals after controlling for Framingham risk score ( P =0.025 and 0.015, respectively). These markers were not predictive of carotid artery thickening in controls. Our study indicates that monocyte surface markers may serve as novel predictors of CVD in HIV‐positive individuals and is consistent with an important role for monocyte activation in the progression of HIV‐related cardiovascular pathology.